Upaya Memulihkan Hak-hak Perempuan: FIAP Kanada dalam Upaya Penurunan Gender-Based Violence di Afghanistan - Kanya Sepasthika Ramadhani (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
Canada as a country highly committed to promoting gender equality and women's empowerment, launched the Feminist International Assistance Policy (FIAP) in 2017 under the leadership of Prime Minister Justin Trudeau. The Feminist International Assistance Policy (FIAP) is a feminist-based foreign policy that focuses on gender equality and women's empowerment. In this case, FIAP's foreign policy is considered to be the best solution for Canada to overcome existing poverty and inequality. Afghanistan is one of the target countries for receiving Canadian FIAP assistance. Given the high percentage of Gender-Based Violence (GBV) phenomena and discrimination in Afghanistan, Canada is also trying to help reduce the level of GBV and discrimination in Afghanistan through the FIAP policy program. With this the author is interested in identifying various forms of cooperation carried out by Canada and Afghanistan in efforts to combat gender-based violence in Afghanistan, as well as explaining how a feminist perspective views Canadian FIAP policies. The scope of this research is during the period of Prime Minister Justin Trudeau's government from 2018 to 2020. This research uses qualitative methods to explain how feminist-based foreign policies can affect the level of reduction of gender-based violence, and uses congruent methods as an analytical technique. The theory of liberal feminism, Gender-Based Violence, the concept of Gender Equality, Gender Mainstreaming, and Feminist Foreign Policy will be used in this research as a knife of analysis. The results of the study show that with the Feminist International Assistance Policy (FIAP) as a manifestation of liberal feminism, Canada will promote gender equality and empower women through various existing programs and policies so that it can have an impact on reducing the level of gender-based violence in Afghanistan.